Enhanced Gut-Homing Dynamics and Pronounced Exhaustion of Mucosal and Blood CD4+ T Cells in HIV-Infected Immunological Non-Responders - Lorvik, Kristina Berg; Meyer-Myklestad, Malin Holm; Kushekar, Kushi; Handeland, Charlotte; Medhus, Asle Wilhelm; Lund-Iversen, Marius; Stiksrud, Birgitte; Kvale, Dag; Dyrhol-Riise, Anne Margarita; Taskén, Kjetil; Reikvam, Dag Henrik (Frontiers in Immunology, 2021)
Immunological non-responders (INR), a subgroup of people living with HIV (PLHIV) who fail to restore CD4+ T cell numbers upon effective antiretroviral treatment, have impaired gut mucosal barrier function and an inferior clinical prognosis compared with immunological responders (IR). The contribution of gut-homing and exhaustion of mucosal T cells to the INR phenotype was previously unknown. Flow cytometry analysis of mononuclear cells from peripheral blood and ileal and colonic lamina propria showed that INR had higher fractions of gut-homing CD4+ T cells in blood compared with IR. In addition, gut-homing cells were more likely to display signs of exhaustion in INR. The increased CD4+ T cell exhaustion in INR was ubiquitous and not restricted to subpopulations defined by activation, differentiation or regulatory T cell markers. In INR, colon CD4+ T cell exhaustion correlated negatively with the fraction of CD4+ T cells in the same compartment, this was not apparent in the ileum. The fraction of exhausted mucosal CD4+ T cells correlated with I-FABP and REG3a, markers of enterocyte damage. We conclude that alterations of gut-homing and exhaustion of T cells may contribute to impaired gut immune and barrier functions associated with immunological non-response in PLHIV.